Peningkatan Keterampilan Menulis Kreatif Puisi Bebas Melalui Media Batu bagi Siswa SMPN 15 Mataram - Sahra, Sahra (Jurnal Paedagogy, 2020)
The purpose of this study was to improve the creative writing skills of free poetry through stone media by applying the Jigsaw cooperative learning model. This research method is a classroom action research consisting of two cycles with the research subject, namely students of class VIII A SMPN 15 Mataram. The research instrument used observation and tests. The research data were analyzed using descriptive qualitative and quantitative techniques. The results showed that the use of stone media could improve the creative writing skills of free poetry. The improvement of the quality of the learning process in cycle I showed an average value of 67.5 and 80.5 in cycle II. The average student assessment results were 4.2 with 85% activeness of the total students.